(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
This paper outlines the creation of a house fire alarm using the Global System for Mobile Communications (GSM) Module with the Arduino system. The primary objective is to avoid fire in order to ensure safety at home Residents and buildings within the home also suffered mishaps. Arduino is used Uno board along with the chip ATmega328. The most important controller utilised is the Temperature sensor ATmega328 that regulates the house fire warning. LM35 Limited To detect fire heat, the temperature sensor is utilised. The user will receive an alert message SMS through GSM module Short Message Service When the system is detected at or above 400 C, an alarm notice will be shown on the LCD display and concurrently an SMS alert will be sent to people at the high temperature in the house. Test results will be documented and discussed. It can assist users enhance safety standards by immediately reacting to accident prevention using this method. In the case of a calamity, this will enable the users to protect life and property.